Approaching Well-Being Through the Research Lens: How HCA Healthcare Colleagues are Building Healthy Work and Learning Environments - Gregory Guldner; Allison Woodall; Deepinder Bal; Jennifer Larkin; Cynthia Borum; Sunny Hull; Annette Edens; Lisa H. Moore; Elaine K. Miller; Harold Gomez Acevedo; Katia M Lugo Enriquez; Noor Judge; et al. (HCA Healthcare Journal of Medicine, 2026)
At the heart of our commitment to the care and improvement of human life are the physicians who dedicate themselves to delivering exceptional care. To support not only our physicians’ professional excellence but also to foster personal fulfillment, HCA Healthcare partnered with Claremont Graduate University to establish the Physician Wellness Research Lab (PWR Lab). In his new role as the Vice President of Academic Affairs for Graduate Medical Education (GME), Dr Guldner led a nationwide search to establish and implement a new approach to well-being. At HCA Healthcare, we believe that true flourishing requires transforming the work and learning environment itself. To guide our approach, we identified 2 complementary theories: Job Demands-Resources (JD-R) Theory and Self-Determination Theory (SDT), which steer the transformation of environments from need-thwarting to need-supporting. Studies conducted in partnership with the PWR Lab confirmed the necessity of a research-driven approach in establishing healthy environments. This work has culminated in the creation of the Resident Experience and Retention Summit (RERS). This teaching workshop is designed for faculty and administrators committed to advancing provider well-being through improvements in the work and learning environment. Participants explore the practical application of SDT and JD-R Theory, following either a clinical or administrative track tailored to their role. Since its launch in 2023, we’ve hosted 6 RERS and have seen meaningful changes in the perception of the work and learning environment across numerous facilities. This internal success in creating supportive environments is mirrored and validated by external, national metrics. For the last 2 years, HCA Healthcare has beaten the national average in each of the 12 well-being items from the Accreditation Council for Graduate Medical Education (ACGME) Survey. At our most recent RERS teaching workshop we showcased poster submissions from both clinical and administrative colleagues highlighting the facility-level initiatives they’ve implemented. We are pleased to share the 8 abstracts featured, each showcasing the practical application of HCA Healthcare’s approach to well-being in diverse health care settings.